Exploring COVID-19 vaccine uptake among healthcare workers in Zimbabwe: A mixed methods study. - Tinotenda Taruvinga; Rudo S Chingono; Edson Marambire; Leyla Larsson; Ioana D Olaru; Sibusisiwe Sibanda; Farirai Nzvere; Nicole Redzo; Chiratidzo E Ndhlovu; Simbarashe Rusakaniko; Hilda Mujuru; Edwin Sibanda; et al. (Public Library of Science (PLoS), 2023)
With COVID-19 no longer categorized as a public health emergency of international concern, vaccination strategies and priority groups for vaccination have evolved. Africa Centres for Diseases Prevention and Control proposed the '100-100-70%' strategy which aims to vaccinate all healthcare workers, all vulnerable groups, and 70% of the general population. Understanding whether healthcare workers were reached during previous vaccination campaigns and what can be done to address concerns, anxieties, and other influences on vaccine uptake, will be important to optimally plan how to achieve these ambitious targets. In this mixed-methods study, between June 2021 and July 2022 a quantitative survey was conducted with healthcare workers accessing a comprehensive health check in Zimbabwe to determine whether and, if so, when they had received a COVID-19 vaccine. Healthcare workers were categorized as those who had received the vaccine 'early' (before 30.06.2021) and those who had received it 'late' (after 30.06.2021). In addition, 17 in-depth interviews were conducted to understand perceptions and beliefs about COVID-19 vaccines. Of the 3,086 healthcare workers employed at 43 facilities who participated in the study, 2,986 (97%, 95% CI [92%-100%]) reported that they had received at least one vaccine dose. Geographical location, older age, higher educational attainment and having a chronic condition was associated with receiving the vaccine early. Qualitatively, (mis)information, infection risk perception, quasi-mandatory vaccination requirements, and legitimate concerns such as safety and efficacy influenced vaccine uptake. Meeting the proposed 100-100-70 target entails continued emphasis on strong communication while engaging meaningfully with healthcare workers' concerns. Mandatory vaccination may undermine trust and should not be a substitute for sustained engagement.